KONTRIBUSI KOORDINASI MATA KAKI DAN KESEIMBANGAN TERHADAP KETERAMPILAN SEPAK SILA PADA EKTRAKURIKULER SEPAK TAKRAW MAN 1 MUARA FAJAR PEKANBARU - ', Sofyan; ', Saripin; agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Looking at the observation, researcher sees some issues while the students were doing the sepak sila technique, those are miss-hit the ball by foot, the ball frequently goes too far while being controlled, the ball was not able to be controlled, the players’ bodies did not stand erectly (unbalance) while controlling the ball that the upcoming ball was not accepted correctly nor controlled. The purpose of this research is to see the contribution of aye-foot and balance coordination to sepak sila skill in takraw extracurricular of MAN 1 Muara Fajar, Pekanbaru. The sample collecting technique used was total sampling with MAN 1 Muara Fajar Pekanbaru’s extracurricular’s students as the population, amounted 10 students as the sample. This test were using correlation technique. Afterward, the data test were done by using normality test, contribution test, significance test α = 0.05. Normality test X1 variable, L0max (0,213) < Ltable (0,258), normality test X2 variable, L0max (0,216) < Ltable (0,258) and normality test Y variable, L0max (0,244) < Ltable (0,258) on the other words, normal data rate and the conclusion of this research shows: there is a significant contribution of ankle coordination, with correlation r= 0.729 where rcount > rtable or 0.729 > 0,632. And the contribution is categorized as a strong contribution. In conclusion, Ho is rejected and Ha is accepted. Keywords : aye-foot coordination, balance, and sepak sila skill